2019
DOI: 10.1136/bmjgast-2019-000282
|View full text |Cite|
|
Sign up to set email alerts
|

Use of ethylene-oxide gas sterilisation to terminate multidrug-resistant bacterial outbreaks linked to duodenoscopes

Abstract: BackgroundCleaning and high-level disinfection have been the standard in the USA and other countries for reprocessing flexible endoscopes, including duodenoscopes and other types of gastrointestinal endoscopes. For decades, this practice has been a cornerstone for infection prevention in the endoscopic setting. However, amid recent reports associating the use of duodenoscopes with infections and outbreaks of carbapenem-resistant Enterobacteriaceae (CRE) and related multidrug-resistant organisms (MDROs), reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
(136 reference statements)
0
19
0
2
Order By: Relevance
“…Factors such as endoscope design, lapses in reprocessing guidelines, damage to the endoscope, or a lack of servicing, maintenance, and repair of the endoscope were hypothesized to be contributors to these outbreaks. 53 In this review, 6 of 17 studies implemented EtO sterilization as an intervention during infectious outbreaks; in at least 3 and possibly 6 studies this intervention yielded an absence of culture positivity from duodenoscopes at all sites, thereby stopping the outbreaks. 6,7,[54][55][56][57] Similar data exist for EtO sterilization ceasing outbreaks attributed to bronchoscopes.…”
Section: Recommendmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as endoscope design, lapses in reprocessing guidelines, damage to the endoscope, or a lack of servicing, maintenance, and repair of the endoscope were hypothesized to be contributors to these outbreaks. 53 In this review, 6 of 17 studies implemented EtO sterilization as an intervention during infectious outbreaks; in at least 3 and possibly 6 studies this intervention yielded an absence of culture positivity from duodenoscopes at all sites, thereby stopping the outbreaks. 6,7,[54][55][56][57] Similar data exist for EtO sterilization ceasing outbreaks attributed to bronchoscopes.…”
Section: Recommendmentioning
confidence: 99%
“…EtO sterilization of duodenoscopes can be an effective tool in some clinical situations, specifically when there are infectious outbreaks observed among patients who have undergone ERCP. A systematic review by Muscarella 53 examined all reported carbapenem-resistant Enterobacteriaceae-and multidrug-resistant organisms-related infections in the United States and Europe attributed to duodenoscope exposure and assessed the adequacy of reprocessing in these outbreaks. Factors such as endoscope design, lapses in reprocessing guidelines, damage to the endoscope, or a lack of servicing, maintenance, and repair of the endoscope were hypothesized to be contributors to these outbreaks.…”
Section: Recommendmentioning
confidence: 99%
“…Bartles et al hypothesized that a second round of high-level disinfection may reduce culture positivity; ultimately, however, no difference was found between single and double high-level disinfection [36]. As a result, some studies have suggested switching to sterilization procedures in order to decrease rates of contamination [37]; however, limitations to this process exist as well [38].…”
Section: Discussionmentioning
confidence: 99%
“…( 38 ) A review of cases worldwide reported that 6 of 23 Carbapenem-Resistant Enterobacteriaceae or MDRO-related outbreaks were treated by adding EtO sterilization; this measure successfully terminated 3 of those 6 outbreaks. ( 39 ) However, there are multiple barriers to widespread use of EtO including cost, potential toxicity to reprocessing staff, and possible damage to endoscopes.…”
Section: Challenges In Endoscope Reprocessingmentioning
confidence: 99%